ENVIRONMENTAL SANITATION, POVERTY AND STUNTING IN INDONESIA - Puspita Sari, Dwi Darma (Journal of Economic Development, Environment and People, 2021)
Abstract. The high population growth is not followed by the growth of infrastructure procurement, which causes the phenomenon of excess demand for clean water and sanitation facilities and infrastructure and also currently Environmental Sanitation in Indonesia is still high, poverty is also high so the behavior of hygiene and sanitation poor food, causing infectious diseases accompanied by disorders such as decreased appetite and vomiting. This condition can reduce the nutritional status of children under five and have negative implications for the progress of child growth (stunting). The purpose of this study is to see the relationship between environmental sanitation, poverty and stunting in 34 provinces in Indonesia for the period 2015-2017. The data used is secondary data during 2015-2017 in 34 provinces in Indonesia. method This uses the analytical approach used is the Granger causality and VAR panel data and spatially uses classic typology. Results: spatially it shows that Indonesia is classified as low stunting and low environmental sanitation (Quadrant III), while in terms of stunting and poverty, it is classified as high stunting and high poverty (Quadrant I) Keywords: Environmental Sanitation, Poverty, Stunting, Hygiene, Nutrition